Cross sectional subcostal echocardiography: atrioventricular septal defects and the short axis cut. Issue 3 (September 1987) - Mortera, C; Rissech, M; Payola, M; Miro, C; Perich, R
Abstract : A short axis echocardiographic cut of the heart from the subcostal approach was used to study the atrioventricular junction in 47 infants and children with congenital heart disease and 20 with normal hearts. Examination of the diastolic openings of both atrioventricular valves was able to establish normal developments of the valves and annuli even when this was found in cases of complex congenital heart disease. In 30 patients with atrioventricular septal defects the technique distinguished between a partial defect (when the two atrioventricular valves were linked transseptally) and a complete defect (when there was only one atrioventricular valve). A range of atrioventricular attachments was seen in these patients. Short axis echocardiography from the subcostal approach reliably identifies different forms of atrioventricular septal defects by defining the anatomy of the atrioventricular valves during maximal diastolic expansion.